Evaluación de la relación entre la carga postural que están sometidos los trabajadores de la empresa PRODUCOM y el riesgo ergonómico - Intriago Intriago, Melissa Geovanna (2019)
The objective of this research was to evaluate the relationship between the postural load to which the workers are subjected and the ergonomic risk in the company PRODUCOM located in Tosagua, province of Manabí, the OWAS Method (Ovako Work Analysis System) was used. , NIOSH (National Institute for Safety and Hygiene at Work) and the Body Map Tool. The data generated by the methods indicated that the most frequent positions were those observed in the crews, with the back bent with arms that are kept below the shoulders, standing on a straight leg and perform a force or load greater than 20 kg. With the results obtained, the idea to be defended was confirmed, since according to the INEN ISO 11228 Standard the company is in the Red Zone "Unacceptable Risk and / or High Risk" due to the data generated by the body map tool that indicated disturbances in the cervical part, lumbar area, shoulders, arms, legs and ankle, which can conceive diseases or injuries that can not be ignored for the workers, for which a preventive and / or corrective measures plan was developed on the identified postural loads that prevent and reduce the ergonomic risk, that is, the presentation of possible Musculoskeletal Disorders (MSD).